Meta-Analysis of Efficacy From CTLA-4 and PD-1/PD-L1 Inhibitors in Cancer Patients - Xu, Li; Yan, Xin; Ding, Weiyue (Frontiers in Oncology, 2022)
Introduction Immune checkpoint inhibitors (ICIs) have been approved to prolong overall survival (OS), compared to other treatments. However, the recent studies reported consistent and inconsistent results. Hence, we conducted this meta-analysis to evaluate the efficacy of ICIs. Materials and Methods The articles were identified by searching PubMed, Embase, and Google Scholar published up to December 2021. A total of 12,126 participants (6,450 cases and 5,676 controls) were involved in the meta-analysis. Median OS and median progression-free survival (PFS) were selected to evaluate the efficacy of cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed cell death 1 (PD-1), and programmed death ligand 1 (PD-L1) inhibitors (ipilimumab, nivolumab or pembrolizumab, and atezolizumab, respectively). Utilizing the random-effect model, hazard ratios (HRs) with 95 confidence intervals (CIs) were calculated by R software. Results We observed a significant association between cancer patients and ICIs in OS (HR = 0.79, CI = 0.74–0.84) and PFS (HR = 0.80, CI = 0.75–0.86). Conclusions The meta-analysis suggested that ICIs were associated with obvious improvements in PFS and OS compared with non-ICI therapies.